2017
DOI: 10.1080/09602011.2017.1387577
|View full text |Cite
|
Sign up to set email alerts
|

We are not the same people we used to be: An exploration of family biographical narratives and identity change following traumatic brain injury

Abstract: Subjective changes are increasingly recognised as important in recovery and rehabilitation following traumatic brain injury. Accumulation of subjective changes over time has led many to examine the question of "continuity of self" post-injury. Vacillation between feeling the same and different is common and often at odds with the medical narrative preparing families for permanent change. This position of ambiguity was examined in a qualitative narrative study. The aim of this paper is to describe the narrative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 58 publications
3
13
0
Order By: Relevance
“…The loneliness among the injured persons related to not remembering what had happened and to others in the family not being able to share the experience. Loneliness in our study can be compared with what is reported in another study as feelings of isolation within the families [25]. Loneliness was also described as a dominant feeling and was either individual or shared and sometimes self-chosen.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…The loneliness among the injured persons related to not remembering what had happened and to others in the family not being able to share the experience. Loneliness in our study can be compared with what is reported in another study as feelings of isolation within the families [25]. Loneliness was also described as a dominant feeling and was either individual or shared and sometimes self-chosen.…”
Section: Discussionsupporting
confidence: 67%
“…This approach is also something we recommend for the whole family together. To help families to realign and reconstruct themselves post-injury might be a helpful strategy for rehabilitation [25]. A problem also described in our study was that STBI survivors demonstrated limitations in verbal expression and narration and thereby perhaps do not experience the positive result expected from these interventions [50].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In contrast to Morriss et al's (2013) study, only one of the fathers reported low self-confidence and self-efficacy in their perceived parenting ability. Another study noted when family narratives were misaligned, survivors feel isolated, experiencing a "moving out" from the family (Whiffin et al, 2017). Similarly, "conflicts and gulfs" in the narratives between family members have been noted to damage relationships (Couchman et al, 2014).…”
Section: Becoming Lost and Finding Their Way Throughmentioning
confidence: 99%
“…The majority of patients were identified as having a Foreclosed identity status (n = 26, 68%), with the next most prominent group being Moratorium (n = 7, 18%), followed by a small number of patients in Diffused (n = 3, 8%) or Achieved (n = 2, 5%; Figure 2). For the surgically naïve group, median (IQR) scores for the EIPQ commitment and exploration scales were 64.5 (14) and 54 (13), respectively. This group was more evenly spread between the Foreclosed (n = 22, 46%) and Diffused (n = 15, 31%) identity statuses, with fewer in Moratorium (n = 5, 10%).…”
Section: Identitystatusatlong-termfollowup:ashiftoutofdiffusedidentitymentioning
confidence: 99%